Implementasi Jambord Dalam Meningkatkan Motivasi Belajar Daring - Hidayat, Ikhwan Mahfud; Yulianti, Rizky Pramita; Siregar, Epi Supriyani (JURNAL PENA EDUKASI, 2022)
Abstract: The purpose of this study is to examine the implementation of jamboard in increasing students' learning motivation. The use of interactive learning media in online learning is crucial. The role of learning media is very important to support the achievement of successful teaching and learning proses. The research method used is descriptive qualitative. By using a qualitative approach, the researchers can understand, observe, analyze, and examine the implementation of jamboard in increasing students' learning motivation. The results of the research findings are as follows: a) Jamboard application can improve student motivation which is manifested in better interactions during learning activities, b) Jamboard application can improve student learning achievement, c) foster students' extrinsic motivation towards learning activities.Keyword: Jamboard; instructional media; online learningAbstrak: Tujuan penelitian ini adalah untuk mengkaji mengenai implementasi jamboard dalam meningkatkan motivasi belajar siswa. Penggunaan media pembelajaran yang interaktif dalam pembelajaran daring sangatlah krusial. Peran media pembelajaran sangat penting guna mendukung ketercapaian keberhasilan kegiatan belajar mengajar. Metode penelitian yang digunakan bersifat deskriptif kualitatif. Dengan pendekatan kualitatif peneliti dapat memahami, mengamati, menganalisa, dan mengkaji tentang penerapan jamboard dalam meningkatkan motivasi belajar siswa. Hasil temuan penelitian adalah sebagai berikut: a) Aplikasi jamboard dapat meningkatkan motivasi siswa yang diwujudkan dalam interaksi selama kegiatan pembelajaran secara lebih baik, b) Aplikasi jamboard dapat meningkatkan prestasi belajar siswa, c) menumbuhkan motivasi ektrinsik peserta didik terhadap kegiatan pembelajaran.Kata kunci: Jamboard; media pembelajaran; pembelajaran daring